Essentials and Controversies in Bariatric Surgery - Huang, Chih-Kun (IntechOpen, 2014)
Bariatric surgery has been proved to be clinically effective and economically viable for obese people when compared to non-surgical interventions. Advancement of minimally invasive surgery in the last 20 years has made the safety and reliability widely accepted by the public and government systems. Bariatric surgery not only proves its efficacy in marked long-term weight loss, but also aids in achieving substantial improvement or remission of co-morbidities. In this book, we review the fundamental knowledge of bariatric surgery, including preoperative nutrition, selection, and surgical complication. In the second part, new emerging and novel procedures are thoroughly described and discussed. Unquestionably, this book will offer you essentials as well as the latest concepts of bariatric and metabolic surgery.